Cloning and expression of E1 and E2 genes of Chikungunya virus in Escherichia coli and baculovirus systems - Anna, Andrew (Universiti Malaysia Sarawak (UNIMAS), 2013)
(Chikungunya fever caused by Chikungunya virus (CHIKV) has re-emerged with large outbreaks in various parts of the world and grabbed the attention of researchers worldwide. Due to lack of simple and rapid diagnostic method for the identification of the virus infection, assessing the epidemic potential and implementing appropriate control measures are often delaye~ In this study, Envelope 1 (E 1) and Envelope 2 (E2) genes of CHIKV from a local isolate were cloned into both E. coli and baculovirus systems as CHIKV -specific diagnostic reagents. The antigenicity of the expressed products was assessed with CHIKV positive and negative patient's sera. Partial CHIKV El and E2 were cloned into E. coli system while complete CHIKV El and E2 were cloned into baculovirus system. All the recombinant proteins were found to be antigenic except for the partial CHIKV E 1 recombinant protein generated by E. coli system. None of the recombinant antigens showed cross reactivity with anti-dengue virus serum sample. These results suggest that the recombinant proteins generated in this study might be useful in the development of diagnostic tools such as ELISA, for the detection of CHlK.V infections. Even though the direct comparison of the two systems is not possible, baculovirus system was seems to be better as they are more compatible with eukaryotic proteins because of similar codon usage rules, providing better expression levels and fewer truncated proteins than in bacteria.